Microstructure and electrical properties of Lu_2O_3-doped ZnO-Bi_2O_3-based varistor ceramics - 徐东 史小锋 程晓农 杨娟 樊曰娥 袁宏明 施利毅 (Transactions of Nonferrous Metals Society of China, 2010)
Lu2O3-doped ZnO-Bi2O3-based varistor ceramics samples were prepared by a conventional mixed oxide route and sintered at temperatures in the range of 900-1 000°C,and the microstructures of the varistor ceramics samples were characterized by X-ray diffractometry（XRD）and scanning electron microscopy（SEM）;at the same time,the electrical properties and V—I characteristics of the varistor ceramics samples were investigated by a DC parameter instrument for varistors.The results show that the ZnO-Bi2O3-based varistor ceramics with 0.3%Lu2O3（molar fraction）sintered at 950°C exhibit comparatively ideal comprehensive electrical properties.The XRD analysis of the samples shows the presence of ZnO,Bi-rich,spinel Zn7Sb2O12 and Lu2O3-based phases.